Observation of the strong electronic coupling in near-infrared-absorbing tetraferrocene aza-dipyrromethene and aza-BODIPY with direct ferrocene-α- and ferrocene-β-pyrrole bonds: Toward molecular machinery with four-bit information storage capacity - Yuriy V. Zatsikha (2018)
© 2017 American Chemical Society. The 1,3,7,9-tetraferrocenylazadipyrromethene (3) and the corresponding 1,3,5,7-tetraferrocene aza-BODIPY (4) were prepared via three and four synthetic steps, respectively, starting from ferrocenecarbaldehyde using the chalcone-type synthetic methodology. The novel tetra-iron compounds have ferrocene groups directly attached to both the α- and the β-pyrrolic positions, and the shortest Fe-Fe distance determined by X-ray crystallography for 3 was found to be ∼6.98 Å. These new compounds were characterized by UV-vis, nuclear magnetic resonance, and high-resolution electrospray ionization mass spectrometry methods, while metal-metal couplings in these systems were probed by electro- and spectroelectrochemistry, chemical oxidations, and Mossbauer spectroscopy. Electrochemical data are suggestive of the well-separated stepwise oxidations of all four ferrocene groups in 3 and 4, while spectroelectrochemical and chemical oxidation experiments allowed for characterization of the mixed-valence forms in the target compounds., while spectroelectrochemical and chemical oxidation experiments allowed for characterization of the mixed-valence forms in the target compounds.. Intervalence charge-transfer band analyses indicate that the mixed-valence [3] + and [4] + complexes belong to the weakly coupled class II systems in the Robin-Day classification. This interpretation was further supported by Mossbauer spectroscopy in which two individual doublets for Fe(II) and Fe(III) centers were observed in room-temperature experiments for the mixed-valence [3] n+ and [4] n+ species (n = 1-3). The electronic structure, redox properties, and UV-vis spectra of new systems were correlated with Density Functional Theory (DFT) and time-dependent DFT calculations (TDDFT), which are suggestive of a ferrocene-centered highest occupied molecular orbital and chromophore-centered lowest unoccupied molecular orbital in 3 and 4 as well as predominant spin localization at the ferrocene fragment attached to the α-pyrrolic positions in [3] + and [4] + .